2018
DOI: 10.1177/0391398818803478
|View full text |Cite
|
Sign up to set email alerts
|

Impact of setup orientation on blend electrospinning of poly-ε-caprolactone-gelatin scaffolds for vascular tissue engineering

Abstract: Introduction: This article explores the effect of horizontal and vertical setups on blend electrospinning with two polymers having vastly different properties-poly-ε-caprolactone and gelatin, and subsequent effect of the resulting microstructure on viability of seeded cells. Methods: Poly-ε-caprolactone and gelatin of varying blend concentrations were electrospun in horizontal and vertical setup orientations. NIH 3T3 fibroblasts were seeded on these scaffolds to assess cell viability changes in accordance with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3
1

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 45 publications
0
19
0
Order By: Relevance
“…The fibre scaffolds were fabricated from a blended polymeric solution. The blends consisted of polycaprolactone (PCL, 80 kDa, Sigma-Aldrich Chemistry Corporate, St. Louis, MI, USA) and gelatin from bovine skin (Type B, ~225 g Bloom, Sigma-Aldrich Chemistry Corporate, St. Louis, MI, USA) in 2,2,2-trifluoroethanol (TFE, 99.8%, abcr GmbH, Karlsruhe, Germany) [ 14 ]. In order to enhance the solubility of gelatin in TFE, 2 v% of acetic acid were added.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fibre scaffolds were fabricated from a blended polymeric solution. The blends consisted of polycaprolactone (PCL, 80 kDa, Sigma-Aldrich Chemistry Corporate, St. Louis, MI, USA) and gelatin from bovine skin (Type B, ~225 g Bloom, Sigma-Aldrich Chemistry Corporate, St. Louis, MI, USA) in 2,2,2-trifluoroethanol (TFE, 99.8%, abcr GmbH, Karlsruhe, Germany) [ 14 ]. In order to enhance the solubility of gelatin in TFE, 2 v% of acetic acid were added.…”
Section: Methodsmentioning
confidence: 99%
“…The mass ratio of PCL to gelatin was 5:2, resulting in 125 mg/mL PCL/TFE and 50 mg/mL gelatin/TFE. The polymeric solution preparation was conducted as previously published by Suresh et al [ 14 ]. Three different fibre scaffolds were manufactured for each of the 13 relative collector velocities of 1.2 to 10.7 m/s at a total process duration of 25 min each (see Figure 1 ) [ 9 , 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…As a result of the constant movement and solvent evaporation, the diameter is constantly decreasing upon deposition on the collector [2,[12][13][14][15][16]. Different parameters like the humidity, temperature, partial pressure of the solvent, concentration of the polymeric solution, viscosity, and conductivity, as well as the surface tension of the solution, the emitter setup, the inner diameter of the emitter, the needle-to-collector distance, the flow rate, the geometry and relative collector velocity of the collector, and the applied electrical field and its distribution, along with the process duration, have a large influence on the electrospinning process [2,[4][5][6][7][8][9][12][13][14][15][16][17][18][19][20][21][22][23]. The recreation of complex tissue structures like tendon-bone junctions call for graded implants with differently oriented fibers [1,10,24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Most recently, a study was conducted on blend electrospinning of PCL and gelatin [ 69 ], investigating the effects of setup orientation on fibre diameter, pore size, and their respective distributions on flat fibre mats. Solutions of different polymer ratios were electrospun, and it was observed that horizontal electrospinning resulted in a homogeneous fibre diameter distribution.…”
Section: State Of the Art—impact Of Apparatus Orientation In Electmentioning
confidence: 99%
“… SEM images of PCL and PCL/gelatin electrospun mats spun in horizontal and vertical setup orientations. (Image from [ 69 ] reproduced with permission from SAGE Publishing). ( a ) 175 mg/mL PCL (horizontal).…”
Section: Figurementioning
confidence: 99%